KnowledgeBoat Logo

Mathematics

Factorise completely using factor theorem :

6x3 - 11x2 - 3x + 2.

Factorisation

1 Like

Answer

Substituting x = 2 in above equation, we get :

⇒ 6(2)3 - 11(2)2 - 3(2) + 2

⇒ 6(8) - 11(4) - 6 + 2

⇒ 48 - 44 - 4

⇒ 0.

∴ x - 2 is the factor of 6x3 - 11x2 - 3x + 2.

On dividing 6x3 - 11x2 - 3x + 2 by (x - 2), we get :

x26x2+x1x2)6x311x23x+2x26x3+12x2x22x3+x23xx2x3+x2+2xx2x3+25x+2x2x3+2x1+x+2x2x3+25x233×\begin{array}{l} \phantom{x - 2}{6x^2 + x - 1} \ x - 2 \overline{\smash{\big)}6x^3 - 11x^2 - 3x + 2} \ \phantom{x - 2}\underline{\underset{-}{}6x^3 \underset{+}{-}12x^2} \ \phantom{{x - 2}2x^3+}x^2 - 3x \ \phantom{{x - 2}x^3+}\underline{\underset{-}{}x^2 \underset{+}{-}2x} \ \phantom{{x - 2}x^3+2-5}-x + 2 \ \phantom{{x - 2}x^3+2-x1}\underline{\underset{+}{-}x\underset{-}{+}2} \ \phantom{{x - 2}x^3+2-5x^233} \times \end{array}

∴ 6x3 - 11x2 - 3x + 2 = (x - 2)(6x2 + x - 1)

= (x - 2)(6x2 + 3x - 2x - 1)

= (x - 2)[3x(2x + 1) -1(2x + 1)]

= (x - 2)(3x - 1)(2x + 1).

Hence, 6x3 - 11x2 - 3x + 2 = (x - 2)(3x - 1)(2x + 1).

Answered By

2 Likes


Related Questions